New World Courtships : Transatlantic Alternatives to Companionate Marriage - Adams-Campbell, Melissa M. (Book collections on Project MUSE., 2015)
"The first scholarly study to recover a geographically diverse array of eighteenth and nineteenth-century countertexts that actively compare culturally diverse marriage practices from Canada to the Caribbean"--